UNDERSTANDING THE FACTORS INFLUENCING BLOCKCHAIN TECHNOLOGY ADOPTION IN MODERN ENTERPRISES - Shinde, Pritam Arunrao; Ubale, Satish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research paper examines the factors influencing the adoption of blockchain technology in modern enterprises, focusing on both internal and external determinants. Conducted with a sample of 231 respondents from various industries, the study investigates how organizational culture, leadership support, technological infrastructure, training resources, communication, regulatory standards, competitive pressures, market maturity, partnerships, and customer expectations affect blockchain technology adoption. Using a quantitative methodology, data were collected through structured questionnaires, and hypotheses were tested using statistical techniques, including one-sample t-tests. The results reveal that internal factors such as organizational culture and leadership support significantly impact blockchain adoption. Concurrently, external factors like regulatory standards, competitive pressures, and customer demands also play a crucial role. The study highlights that organizations with supportive internal environments and those adept at navigating external pressures are more likely to successfully adopt blockchain technology. The findings suggest that a comprehensive approach, addressing both internal and external factors, is essential for effective blockchain integration. Implications for practice include the need for organizations to foster a supportive internal culture, ensure strong leadership, and stay responsive to external regulatory and market dynamics. Future research directions include exploring the long-term impact of blockchain adoption on organizational performance and investigating the integration of blockchain with other emerging technologies.